Convergent Total Synthesis of Histone H2B Protein with Site-Specific Ubiquitination at Lys120 - Qi, Yun-Kun; He, Qiao-Qiao; Ai, Hua-Song; Li, Jia-Bin; Zheng, Ji-Shen (Synlett, 2017)
Histone H2B Lys120 mono-ubiquitylation (H2BK120Ub) plays an important role in regulating gene expression and diverse nuclear processes. For biochemical and biophysical studies of this dynamic post-translational modification, access to homogeneous and workable amount of H2BK120Ub is obligatory. Here we report a new strategy for the convergent total chemical synthesis of homogenous histone H2BK120Ub on multi-milligram scale through the combination of hydrazide-based native chemical ligation and acid-cleavable auxiliary-mediated ligation of peptide hydrazides. The synthetic H2BK120Ub could be efficiently incorporated into nucleosomes, which may provide valuable materials for the biochemical and structural studies of nucleosome complexes involving H2BK120Ub.
Keywords: native chemical ligation; chemical synthesis; histone modification; ubiquitination; H2B; H2BK120